Microparticle clearance theory: An update to the potential mechanisms of action of cupping therapy. Issue 1 (March 2021) - Hassan, Nurudeen; Suleman, Rizwhan; Al-Azzani, Waheeb; Jaber, Hisham; Mahdi, Ali
Abstract: Cupping therapy is an ancient medical practice that dates back as far as the earliest records of human civilisation. Unlike many other ancient therapies, cupping is still widely practised in different parts of the World. The two main forms of cupping; dry cupping and wet-cupping have recently experienced a resurgence in popularity in the West due, in part, to high profile athletes and celebrities undergoing the treatment. Although cupping is widely used by complementary and holistic therapists to treat many conditions, its mechanisms of action are not fully understood. In this paper, we review the current theories and mechanisms through which wet-cupping therapy may exert its effects. We also describe, for the first time the microparticle clearance theory as a novel mechanism through which wet-cupping therapy may exert anti-inflammatory, anti-thrombotic and afford endothelial protection within tissue microvasculature. However, further research is required in order to confirm the exact modes of action of cupping to inform targeted clinical research in the field.